Quantifying the honey bee dance floor: A data-driven method for defining and comparing waggle dance regions - Byron N. Van Nest; Ashley E. Wagner; Michele L. Joyner; Edith Seier; Darrell Moore (PLoS ONE, 2026)
Honey bee ( Apis mellifera ) foragers perform waggle dances inside the hive to communicate the location of profitable foraging sites to nestmates. These recruitment dances occur within a specific region of the comb, known as the dance floor, but its location and structure have historically been described only qualitatively. Here we introduce a data-driven geometric method to define and quantify the dance floor from waggle-dance coordinates. The approach combines convex hulls and confidence ellipses to produce a closed region representing the area of highest dance density and yields interpretable spatial metrics including centroid location, area, perimeter, major and minor axes, and orientation. To demonstrate the method’s performance, we applied it to 155 observations of eight colonies in observation hives differing in size and date. Using complementary univariate and multivariate analyses, the framework consistently captured approximately 91% of dances, matching historical estimates based on entrance distance, and detected systematic differences among observations associated with hive size, day, and time (e.g., size-dependent shifts in centroid position and width, and time-of-day effects on orientation), illustrating its sensitivity to experimental and temporal context. This work provides an explicit quantitative definition of the honey bee dance floor and a reproducible analytical framework for comparing spatial recruitment patterns across colonies, environments, and future experimental designs.